If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20(5) = 20q + 5 Multiply 20 * 5 100 = 20q + 5 Reorder the terms: 100 = 5 + 20q Solving 100 = 5 + 20q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-20q' to each side of the equation. 100 + -20q = 5 + 20q + -20q Combine like terms: 20q + -20q = 0 100 + -20q = 5 + 0 100 + -20q = 5 Add '-100' to each side of the equation. 100 + -100 + -20q = 5 + -100 Combine like terms: 100 + -100 = 0 0 + -20q = 5 + -100 -20q = 5 + -100 Combine like terms: 5 + -100 = -95 -20q = -95 Divide each side by '-20'. q = 4.75 Simplifying q = 4.75
| 8n-2=19+5n | | 6t-12-(3t-3)=-19 | | 2(x-1)+3(x+2)=5x+4 | | 2(2x)+47=2(2x)+47 | | -40+3x=10+2x | | 6x-12=5x+17 | | 6(y-24)-6y=0 | | -40+3x=2x | | 4*x-17=23 | | 4x+x^2=179 | | 6-x=10-2x | | 4y+4x=12 | | 2x+x+2(2)+75=180 | | 20=16(16)+b*b | | 11x-66=7x+34 | | 5gf^2+g^2f+15gf= | | 9(2p-1)= | | 9t=-2t^3-9t^2 | | 4y^2-18y+21=0 | | 7x+18=4x+30 | | 43-[4+9y-3(y+5)]=-5(2y+3)-[6(y-1)-3y+2] | | 31792.5=3.14*r^2 | | 36=-4(x-3) | | 2n^2=-24-19n | | y+7x=28 | | 4(7x)+8(4y)-3(5x)+2x+5y+x-7-5-10y= | | 5br-25b+2r-10= | | cosx=0.3x | | 3=8d-13 | | 20t-9.8t^2=0 | | 4(4)+a*a=5 | | 6(a-2)=9a-3(2a-1) |